Exploring the Conceptual Definition of Islamic Financial Literacy from the Quran and Sunnah - Ab Rashid, Rosemaliza; Zainol, Zairani; Isa, Mohamad Yazid; Mohd Taib, Hasniza; Khairol Nizam, Aini Nur Hajjar (The Mattingley Publishing Co., Inc., 2019)
The recurring financial crisis calls for increasing attention on the crucial role of financial literacy. Recent literature covering both theoretical and empirical work on financial literacy mainly focus on the conventional perspective of financial literacy. Since some of the elements are not compatible with the rapidly growing segment of the Islamic financial services industry, there is a pressing need to explore the concept of financial literacy from the Shariah perspective. This paper seeks to explore the conceptual definition of financial literacy from the basic sources of Shariah, namely, the Quran and the Sunnah. Thus, a qualitative approach involving in-depth interviews were employed to achieve the objective of the study. Next, a qualitative data analysis approach involving data condensation, data display, conclusion drawing were carried out. The findings of the analysis reveal that the Shariah primary sources do provide a comprehensive and sound economic guidance on prudent wealth and financial management at the individual level. Thus, Islamic financial literacy can be broadly defined as management of wealth and finance according to the Shariah, which are based on the following broad themes, namely, principle of moderation, spending based on priority, compulsory and voluntary spending, saving and investment, prudent use of debt. A sufficient understanding of these themes will promote sound financial management behavior and practices. Thus, there must be a concerted effort by policy makers, government agencies, higher education providers, industry players as well as religious teachers to widely disseminate the Shariah guidance on proper management of wealth to all levels of the society through workshops, seminars, religious classes, employee training as well embedded in the school and tertiary education curriculum